Analisis Kemampuan Pemecahan Masalah Matematis Pada Materi Sistem Persamaan Linear Tiga Variabel (SPLTV) Di SMA PGRI 4 Jakarta - Laelasari Laelasari (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study aims to analyze students' mathematical problem-solving abilities in the topic of Systems of Three Linear Equations (SPLTV) at SMA PGRI 4 Jakarta. The research employs a qualitative method with an approach that includes interviews and written tests. The subjects of the study consist of eleventh-grade students selected purposively. The results indicate that students have varying levels of understanding regarding SPLTV problems, with some students facing difficulties in comprehending word problems and applying appropriate solving methods. Nevertheless, most students are able to utilize substitution, elimination, and combination methods in solving problems. The study also finds that students tend not to check their answers, which can affect the accuracy of their results. Therefore, it is recommended that students adopt a more systematic approach in problem-solving and perform checks to enhance their confidence and answer accuracy.